2003
DOI: 10.1152/ajpheart.01047.2002
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H oxidase-generated superoxide anion accounts for reduced control of myocardial O2 consumption by NO in old Fischer 344 rats

Abstract: We investigated the role of nitric oxide (NO) in the control of myocardial O2 consumption in Fischer 344 rats. In Fischer rats at 4, 14, and 23 mo of age, we examined cardiac function using echocardiography, the regulation of cardiac O2 consumption in vitro, endothelial NO synthase (eNOS) protein levels, and potential mechanisms that regulate superoxide. Aging was associated with a reduced ejection fraction [from 75 +/- 2% at 4 mo to 66 +/- 3% (P < 0.05) at 23 mo] and an increased cardiac diastolic volume [fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 32 publications
7
89
0
Order By: Relevance
“…26 Furthermore, we reported that NO-dependent control of V O 2 was attenuated in cardiac muscle from SOD2 ϩ/Ϫ mice, which was reversed by the freely membrane-permeable O 2 Ϫ scavenger Tiron. 17 Our previous in vitro studies 17,25,26 have shown that O 2 Ϫ plays an important role in the regulation of NOdependent control of V O 2 . These studies support our present finding that increased O 2 Ϫ in skeletal muscle reduces NO bioavailability and NO-dependent control of V O 2 in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…26 Furthermore, we reported that NO-dependent control of V O 2 was attenuated in cardiac muscle from SOD2 ϩ/Ϫ mice, which was reversed by the freely membrane-permeable O 2 Ϫ scavenger Tiron. 17 Our previous in vitro studies 17,25,26 have shown that O 2 Ϫ plays an important role in the regulation of NOdependent control of V O 2 . These studies support our present finding that increased O 2 Ϫ in skeletal muscle reduces NO bioavailability and NO-dependent control of V O 2 in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…NO-dependent control of V O 2 in cardiac muscle from old Fisher 344 rats, a model of accelerated aging, was reduced and was associated with NAD(P)H oxidase-generated O 2 Ϫ . 25 Angiotensin II at pathophysiological concentrations stimulates an increase in O 2 Ϫ through the activation of NAD(P)H oxidase and attenuates NO-dependent control of V O 2 in cardiac muscle from normal dogs. 26 Furthermore, we reported that NO-dependent control of V O 2 was attenuated in cardiac muscle from SOD2 ϩ/Ϫ mice, which was reversed by the freely membrane-permeable O 2 Ϫ scavenger Tiron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have also described increased ROS production in the carotid arteries and aorta of aged rats [41,42] and mice [43]. Aging-induced vascular oxidative stress is characterized by a down-regulation of antioxidants, such as ecSOD [40], an increased expression of iNOS [1,43] and increased activity of NAD(P)H oxidases [7,42,44] and/or other oxidase mechanisms [45]. Increased oxidative stress in aging leads to functional inactivation of NO via increased O 2 ·− levels yielding in an increase in formation of a reactive oxidant ONOO − , which may impair cardiovascular function through multiple mechanisms [7,40,43,44,46,47].…”
Section: Anti-oxidant Effects Of Resveratrolmentioning
confidence: 99%
“…·O 2 − further dismutates to H 2 O 2 and ·OH, the latter being highly toxic to biological tissues, causative of significant myocardial necrosis and apoptosis. Several recent studies report that aging increases reactive oxygen species (ROS) (Adler et al 2003;Jacob et al 2010a;Jacob et al 2010b;Judge et al 2005). Leeuwenburgh and colleagues demonstrate increased mitochondrial ROS formation with aging (Judge et al 2005).…”
Section: Introductionmentioning
confidence: 99%